Therapeutic strategy for lower limb lymphedema and lymphatic fistula after resection of a malignant tumor in the hip joint region: A case report. Issue 3 (1st August 2013) - Hara, H.; Mihara, M.; Hayashi, A.; Kanemaru, M.; Todokoro, T.; Yamamoto, T.; Iida, T.; Hino, R.; Koshima, I.
<x xml:space="preserve">Abstract</x> Lymphatic fistula complicating lymphedema is thought to occur due to communication between lymph vessels and the skin, which has yet to be shown objectively. The objective of this case report is to show the pathology and treatment using simultaneous lymphatic fistula resection and lymphatico‐venous anastomosis (LVA). A 40‐year‐old woman underwent extended resection and total hip arthroplasty for primitive neuroectodermal tumor in the right proximal femur 23 years ago. Right lower limb lymphedema developed immediately after surgery and lymphatic fistula appeared in the posterior thigh. On ICG lymphography, lymph reflux toward the distal side dispersing in a fan‐shape reticular pattern from the lymphatic fistula region was noted after intracutaneous injection of ICG into the foot. We performed simultaneous lymphatic fistula resection and of LVA. Pathological examination showed that the epidermis and stratum corneum of the healthy skin were lost in the lymphatic fistula region. Dilated lymph vessels were open in this region. The examinations provide the first objective evidence that the cause of lymphatic fistula may be lymph reflux from lymphatic stems to precollectors through lymphatic perforators. © 2013 Wiley Periodicals, Inc. Microsurgery 34:224–228, 2014.